Reply to: Intergenerational nutrition benefits of India’s national school feeding program: Reality or a bridge too far? - Chakrabarti, Suman; Scott, Samuel P.; Alderman, Harold; Menon, Purnima; Gilligan, Daniel O. (Nature Publishing Group, 2022)
We thank Sachdev et al. for engaging with our original article that explored whether India’s national school feeding program has intergenerational nutrition benefits. Here, we reply to the critiques raised in their Matters Arising (MA) and clarify important aspects of our work related to: (1) the exposure, (2) the pathway from exposure to outcome, (3) the interpretation of the program contribution to future child nutrition, (4) the role of the program in a context of increasing noncommunicable diseases.